Evaluating the Impact of Guided Inquiry Learning on Analytical Skills in Civics Education - Sofy, Malik (AIM: Journal of Islamic Education Management, 2023)
This research is undertaken with the primary objective of enhancing the analytical skills of eighth-grade students at MTs Negeri 2, Cirebon, particularly in the domain of the Functions of the 1945 Constitution and Other Legislation. The research design is grounded in the Classroom Action Research methodology as conceptualized by Kemmis & McTaggart, encompassing four distinct phases: planning, implementation, observation, and reflection. The study unfolds across two cycles, each comprising two instructional sessions, and involves a cohort of 32 students from the eighth grade at MTs Negeri 2, Cirebon. The findings of this research underscore the efficacy of the guided inquiry model in bolstering the analytical competencies of students. These conclusions are derived from the tangible outcomes represented by average scores and completion percentages. Insight gained through observational analysis during the guided inquiry model application reveals that students not only grasp the intricacies of the Functions of the 1945 Constitution and other legislation but also exhibit the ability to dissect various sections of these legal documents. The analytical skills assessment results demonstrate that in Cycle I, students achieved an average score of 71.25 with a completion rate of 68.75%. Subsequent to the intervention in Cycle II, the average score increased to 80.59, with a notable improvement in the completion rate to 95.75%. This affirms the successful impact of the guided inquiry model on elevating studentsâ€™ analytical capabilities concerning the Functions of the 1945 Constitution and Other Legislation.Â Â